PROBLEM OF CULTURE: ELT IN A PAKISTANI CONTEXT - Muhammad Abdullah (European Scientific Journal, ESJ, 2014)
This paper reports on a comprehensive study conducted in investigation of perceptions and practices of integrating an important aspect of language teaching—culture—in Pakistani EFL classrooms. It involved both qualitative and quantitative investigation into the issue in order to understand the phenomenon in totality. The results revealed a highly positive attitude of teachers in favor of incorporating culture teaching along with language teaching, but at the same time the dominant opinion was to adapt language teaching materials in order to suit local audiences.